Simile Figurative Language in Passenger Selected Song - Manik Sancita (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This article discusses about simile figurative language in selected song lyrics of Passenger. The writer analysed five song’s lyrics of Passenger which is used as data source. The five song’s lyrics are and I Love Her, I Hate, The Wrong Direction, Things that Stop You Dreaming, Beautiful Birds. The data in this article analysed in a descriptive and qualitative way. The purpose of this article is to identify the language and meaning of the metaphorical similes found in the lyrics of selected passenger songs. The article used theory proposed by Knickerbocker and Reninger (1963) and theory proposed by Leech (1981). The result of this article found fourteen similes in the songs’ lyrics which centred around connotative and affective meaning.